2015
DOI: 10.4028/www.scientific.net/amr.1087.475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sintering Temperature on Biphasic Calcium Phosphate (BCP) Biocomposite

Abstract: The present report aims to fabricate biphasic calcium phosphate (BCP) biocomposite in order to study the effects of sintering temperature on the sintered BCP biocomposite characteristics (phase’s formation, porosity and hardness properties). These effects were quantified using design of experiment (DOE) to develop mathematical models. BCP biocomposite pellets (60 wt% HA) were fabricated using mixing, pressing and sintered at two different temperatures (1100°C and 1250°C). The experiment was run by following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…However, we found that the group with peak temperature lasting for 2 hours at 1250 °C showed the highest strength, both at ultimate and at fracture point. As previously shown by other authors [ 14 , 15 , 16 ], the ultimate stress achieved by samples that were sintered at the peak temperature of 1250 °C for longer times was significantly lower. This was shown to be due, for times longer than 2 hours at peak temperatures above 1200 °C, to allotropic transformation of TCP from β to α phase, shown to occur by XRD; in fact, the α phase is brittle and with reverse transformation, is not totally achieved during cooling to room temperature [ 14 , 16 ].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, we found that the group with peak temperature lasting for 2 hours at 1250 °C showed the highest strength, both at ultimate and at fracture point. As previously shown by other authors [ 14 , 15 , 16 ], the ultimate stress achieved by samples that were sintered at the peak temperature of 1250 °C for longer times was significantly lower. This was shown to be due, for times longer than 2 hours at peak temperatures above 1200 °C, to allotropic transformation of TCP from β to α phase, shown to occur by XRD; in fact, the α phase is brittle and with reverse transformation, is not totally achieved during cooling to room temperature [ 14 , 16 ].…”
Section: Discussionsupporting
confidence: 80%
“…Compressive strengths of cancellous bone were found in the range of 2–12 MPa [ 50 , 51 ], depending on the skeletal site; thus, developing constructs as scaffolds with mechanical strength similar to the hosting bone is of paramount importance. Indeed, mechanical properties of BCP biomaterials have been studied for several years in order to increase their performance after grafting in jawbone [ 11 , 12 , 13 , 16 , 17 , 18 , 19 ]. The mechanical testing performed in the present study did not show a relevant variability depending on the time of permanence at the peak temperature for samples of groups at T = 1200 °C; conversely, for groups at T = 1250 °C, yield, ultimate, and fracture stresses seemed to decrease as the duration of the sintering increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations